Human iPSC-derived blood-brain barrier microvessels: validation of barrier function and endothelial cell behavior. (January 2019) - Linville, Raleigh M.; DeStefano, Jackson G.; Sklar, Matt B.; Xu, Zinnia; Farrell, Alanna M.; Bogorad, Max I.; Chu, Chengyan; Walczak, Piotr; Cheng, Linzhao; Mahairaki, Vasiliki; Whartenby, Katharine A.; Calabresi, Peter A.; et al.
Abstract: Microvessels of the blood-brain barrier (BBB) regulate transport into the brain. The highly specialized brain microvascular endothelial cells, a major component of the BBB, express tight junctions and efflux transporters which regulate paracellular and transcellular permeability. However, most existing models of BBB microvessels fail to exhibit physiological barrier function. Here, using (iPSC)-derived human brain microvascular endothelial cells (dhBMECs) within templated type I collagen channels we mimic the cylindrical geometry, cell-extracellular matrix interactions, and shear flow typical of human brain post-capillary venules. We characterize the structure and barrier function in comparison to non-brain-specific microvessels, and show that dhBMEC microvessels recapitulate physiologically low solute permeability and quiescent endothelial cell behavior. Transcellular permeability is increased two-fold using a clinically relevant dose of a p-glycoprotein inhibitor tariquidar, while paracellular permeability is increased using a bolus dose of hyperosmolar agent mannitol. Lastly, we show that our human BBB microvessels are responsive to inflammatory cytokines via upregulation of surface adhesion molecules and increased leukocyte adhesion, but no changes in permeability. Human iPSC-derived blood-brain barrier microvessels support quantitative analysis of barrier function and endothelial cell dynamics in quiescence and in response to biologically- and clinically-relevant perturbations.